PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT JESINDO SARANA USAHA JAKARTA SELATAN - Sephia Ananda; Indra (Jurnal Menara, 2025)
This study aims to test the effect of recruitment and training on employee performance at PT Jesindo Sarana Usaha. The method in this study uses quantitative research methods. The number of samples is 50 respondents. Using data collection techniques, observation, and distribution of questionnaires using SPSS version 26. Data processing and analysis techniques use descriptive analysis, data instrument testing, classical assumption tests, correlation and determination tests, hypothesis tests. The results of this study are that recruitment has a significant positive partial effect on employee performance with the regression equation recruitment has a significant effect on employee performance with the regression equation Y = 7.768 + 0.765 (X1). Based on the results of the hypothesis test, the calculated t value> t table 9.895 or (9.895> 2.010) is obtained. Thus Ho1 is rejected and Ha1 is accepted, meaning that there is a significant effect of recruitment on employee performance. Training has a significant effect on employee performance with the regression equation Y = 7.165 + 0, 800 X2. Based on the results of the hypothesis test, the calculated t value is > t table (13.180 > 2.010). Thus Ho2 is rejected Ha2 is accepted, meaning that there is a significant positive influence between training and employee performance. Recruitment and training are positively significant to employee performance with the regression equation Y = 6.523 + 0.110 (X1) + 0.704 (X2). The hypothesis test obtained the calculated F value > F table or (86.389 > 3.19). Thus Ho3 is rejected and Ha3 is accepted meaning that there is a significant influence of recruitment and training on employee performance.